1983
DOI: 10.1161/01.str.14.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow and vascular reactivity in collaterally perfused brain tissue. Evidence of an ischemic penumbra in patients with acute stroke.

Abstract: SUMMARY In a group of 48 patients with completed stroke, 8 patients had viable collaterally perfused brain tissue which was accessible for rCBF recordings with a two dimensional technique. All 8 had deep subcortical infarcts on CT-scan, and angiograpic occlusion of the arteries normally supplying the infarcted territory. The brain tissue overlying the deep infarcts appeared normal on CT-scan and was supplied by collateral circulation. rCBF was measured in all within 72 hours after the stroke. The intra-carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
2
3

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(121 citation statements)
references
References 24 publications
3
113
2
3
Order By: Relevance
“…In animal models, neurones within this region predominantly necrose 24 to 48 h after the occlusion of the blood vessel [22,23]. The cortical region at the fringes of the MCA territory, with limited ancillary microvascular perfusion of nutrients from surrounding tissue [24][25][26], has been shown in some studies to provide an environment in which apoptosis can predominate [3-7, 11, 12, 27]. From a therapeutic viewpoint, these apoptotic cortical neurones provide the greatest opportunity for intervention and a number of studies have examined the efficacy of compounds targeted against the apoptotic cascade [8,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, neurones within this region predominantly necrose 24 to 48 h after the occlusion of the blood vessel [22,23]. The cortical region at the fringes of the MCA territory, with limited ancillary microvascular perfusion of nutrients from surrounding tissue [24][25][26], has been shown in some studies to provide an environment in which apoptosis can predominate [3-7, 11, 12, 27]. From a therapeutic viewpoint, these apoptotic cortical neurones provide the greatest opportunity for intervention and a number of studies have examined the efficacy of compounds targeted against the apoptotic cascade [8,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Neu rological recovery has been associated with sur gical reversal of hemodynamic focal ischemia de fined with PET (Baron et aI., 1981). Studies in humans using the xenon-133 inhalation method have demonstrated blood flows in the range charac teristic of the ischemic penumbra and loss of auto regulation in large zones with normal appearance on computed tomography (CT) scan following deep cerebral infarcts (Olsen et al, 1983). Recent discus sions of the ischemic penumbra have emphasized the dynamic nature of the situation.…”
Section: Discussionmentioning
confidence: 99%
“…This unstable situation can resolve or may progress to infarction, with the patient's ultimate deficit de pendent on the outcome (Olsen et al, 1983;Kushner et al , 1987).…”
mentioning
confidence: 99%
“…Experimentally, total ischaemia (cerebral blood flow < 1.5 ml 100 g-1 min-1) may be briefly tolerated before cell death becomes inevitable, but increasing duration of ischaemia diminishes cell survival (Jones et al, 1981). Whereas cerebral blood flow below 10 ml 100 g-1 min-1 is nearly always associated with cell death, cerebral blood flow values between 10 and 18 ml 100 g-1 min-1 (Sharbrough, 1973) or perhaps up to 23 ml 100 g-1 min-1 (Olsen et al, 1983), may result in reversible loss of electrical activity ( Table 1). The ischaemic penumbra is thus the rim of tissue around an area of infarction, which is receiving blood flow within this range of approximately 10-18 ml 100 g-1 min-1.…”
Section: Haemodynamic and Vascular Mechanismsmentioning
confidence: 99%